.. _discrete_sine_transform: ####################### Discrete sine transform ####################### As we did to derive :ref:`the discrete cosine transform `, we consider a shifted discrete Fourier transform of :math:`2 N` real numbers. Here, instead of the even symmetry, we consider a signal satisfying the odd symmetry: .. math:: x_{2 N - 1 - n} = - x_n under :math:`\seq{n}{0}{1}{2 N - 1}`. Due to .. math:: \sum_{n = N}^{2 N - 1} x_n \twiddle{- 2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} = - \sum_{n = 0}^{N - 1} x_n \twiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N}, .. derivation_disclosure:: With :math:`m = 2 N - 1 - n`, we have .. math:: \sum_{m = N - 1}^{0} x_{2 N - 1 - m} \twiddle{- 2 \pi}{\left( 2 N - 1 - m + \frac{1}{2} \right) k}{2 N} & = - \sum_{n = 0}^{N - 1} x_n \exp \left( - 2 \pi k I \right) \twiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} & = - \sum_{n = 0}^{N - 1} x_n \twiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N}. we obtain .. math:: X_k = - 2 I \sum_{n = 0}^{N - 1} x_n \stwiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N}. It is clear that :math:`X_k \in \mathbb{I}`. Note that .. math:: X_{2 N - k} = X_k, .. derivation_disclosure:: .. math:: X_{2 N - k} & = - 2 I \sum_{n = 0}^{N - 1} x_n \stwiddle{2 \pi}{\left( n + \frac{1}{2} \right) \left( 2 N - k \right)}{2 N} & = - 2 I \sum_{n = 0}^{N - 1} x_n \sin \left( \pi \left( 2 n + 1 \right) - 2 \pi \frac{\left( n + \frac{1}{2} \right) k}{2 N} \right) & = - 2 I \sum_{n = 0}^{N - 1} x_n \stwiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} \,\, \left( \because \cos \left\{ \pi \left( 2 n + 1 \right) \right\} = -1 \right) & = X_k. and thus it is sufficient to consider :math:`\seq{k}{0}{1}{N}`. Additionally we easily see that :math:`X_0 \equiv 0`. The inverse transform can be found as follows; due to .. math:: \sum_{k = N}^{2 N - 1} X_k \twiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} = - \sum_{k = 1}^{N - 1} X_k \twiddle{- 2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} + \left( -1 \right)^n I X_N, .. derivation_disclosure:: .. math:: \sum_{k = N}^{2 N - 1} X_k \twiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} & = \sum_{k = N}^{2 N - 1} X_{2 N - k} \twiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} & = \sum_{l = N}^{1} X_l \twiddle{2 \pi}{\left( n + \frac{1}{2} \right) \left( 2 N - l \right)}{2 N} \,\, \left( l \equiv 2 N - k \right) & = \sum_{k = 1}^{N} X_k \exp \left\{ \pi \left( 2 n + 1 \right) I \right\} \twiddle{- 2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} & = - \sum_{k = 1}^{N} X_k \twiddle{- 2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} \,\, \left( \because \exp \left\{ \pi \left( 2 n + 1 \right) I \right\} = -1 \right) & = - \sum_{k = 1}^{N - 1} X_k \twiddle{- 2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} + \left( -1 \right)^n I X_N. we obtain .. math:: x_n & = \frac{1}{2 N} \left\{ \sum_{k = 0}^{N - 1} X_k \twiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} - \sum_{k = 1}^{N - 1} X_k \twiddle{- 2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} + \left( -1 \right)^n I X_N \right\} & = \frac{I}{N} \left\{ \sum_{k = 1}^{N - 1} X_k \stwiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} + \left( - 1 \right)^n \frac{X_N}{2} \right\}. By substituting :math:`X_k` with :math:`- I X_k`, we find the forward transform: .. math:: X_k = 2 \sum_{n = 0}^{N - 1} x_n \stwiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} and the backward transform: .. math:: x_n = \frac{1}{N} \left\{ \sum_{k = 1}^{N - 1} X_k \stwiddle{2 \pi}{\left( n + \frac{1}{2} \right) k}{2 N} + \left( - 1 \right)^n \frac{X_N}{2} \right\}. To eliminate the case of :math:`k = 0` (:math:`X_0 \equiv 0`), we shift :math:`k` and finally we obtain the discrete sine transform of type II and type III: .. math:: X_k = 2 \sum_{n = 0}^{N - 1} x_n \stwiddle{ 2 \pi }{ \left( n + \frac{1}{2} \right) \left( k + 1 \right) }{ 2 N } for :math:`\seq{k}{0}{1}{N - 1}`, and .. math:: x_n = \frac{1}{N} \left\{ \sum_{k = 0}^{N - 2} X_k \stwiddle{2 \pi}{\left( n + \frac{1}{2} \right) \left( k + 1 \right)}{2 N} + \left( - 1 \right)^n \frac{X_{N - 1}}{2} \right\} for :math:`\seq{n}{0}{1}{N - 1}`, respectively. Note that both transforms are :math:`\mathbb{R}^N \rightarrow \mathbb{R}^N`.